Vibration Analysis and Optimal Control of Hydraulic Turbine Based on Sliding Mode Control Strategy - Xiaoping Huang; Yaqiong Zhang; Wenzhe Huang (IEEE Access)
The turbine generator unit plays a very important role in maintaining the stability of the power system and improving the quality of power. However, hydropower units will bring the risk of low-frequency oscillation or ultra-low frequency oscillation to the power system, threatening the stable operation of the power grid. Therefore, it is necessary to deeply study the mechanism of low-frequency oscillation of hydropower units, analyze the adverse factors to the system and adjust and control them. In this paper, a speed change method based on exponential rules is proposed on the basis of the traditional axial flow turbine model, and a coupling model of fuzzy sliding mode control of the turbine is constructed. A control strategy combining fuzzy logic and sliding mode is adopted to adjust the convergence speed according to the change of working conditions and working points by using mechanical power. By incorporating the angle and voltage variables into the sliding mode function design, the influence of controller output on system damping is improved, and the stability of working angle output is improved. The simulation results under various working conditions show that the control law can suppress the low-frequency oscillation of the system when the system is subjected to power disturbance, effectively improve the power angle oscillation behavior of the hydropower unit, significantly improve the stability of the system and the robustness of the controller, and verify the effectiveness and feasibility of the designed controller’s power angle oscillation suppression ability. It provides theoretical support and a new solution for suppressing low frequency oscillation of hydro-generator set.